Faktor-Faktor Yang Berhubungan Dengan Biaya Penerapan Rujukan Elektronik Aplikasi P-Care Di Kota Makassar - Hadrianti H. D. Lasari; Era Pratiwi; Rini Aryani Yamin (HB PRESS, 2019)
Health workers in Indonesia's primary health care use electronic references on the P-care application. Referral is the large number of sufferers who come to the unit through referrals from the government, health workers, police and law. This study uses an electronic reference P-Care in 35 Primary Health Care in Makassar City. This research was a cross sectional analytic study using an online questionnaire instrument that was distributed to 46 Primary Health Care, and 35 questionnaires were filled out. Result, related gender with cost of applying the value of p = 0.39, related the age aspect with cost of applying with a value of p = 0.59, the level of education p = 0.92 and years of service p = 0.6. relationship between sex, age, level of education and years of service with changes or developments using electronic P-Care referrals at the Puskesmas. After conducting statistical tests using the chi-square, it was found that for gender to significant changes in the value of p = 0.01, the age aspect of significant changes with a value of p = 0.88, the level of education towards significant changes with a value of p = 0.42 and years of service to significant changes with a value of p = 0.60.